2022
DOI: 10.1002/pssr.202200054
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Nanocomposites for Low Power Phase‐Change Memory: GeTe/C Multilayers

Abstract: Innovative nanocomposites consisting of [(GeTe)4 nm/C1 nm]10 multilayers (MLs) deposited by magnetron sputtering are integrated in phase‐change memory (PCM) test devices with a “wall structure.” Scanning transmission electron microscopy (STEM) shows that an ML structure, with crystallized GeTe layers, is kept after integration in as‐fabricated devices and also after an additional annealing of the devices at 425 °C. The programming current (RESET current) required to reach the high resistance state of [(GeTe)4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Indeed, we have recently succeeded in integrating a [GeTe 4 nm/C 1 nm] 10 ML into phase-change memory test devices and have observed a significant improvement in programming performances. 37 A reduction in the RESET current of about 55% and in drift coefficient of about 40% in ML devices annealed at 425 °C were observed in comparison with similar devices incorporating the Ge 2 Sb 2 Te 5 reference PCM. Similar trends have been observed in devices based on GST/C MLs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Indeed, we have recently succeeded in integrating a [GeTe 4 nm/C 1 nm] 10 ML into phase-change memory test devices and have observed a significant improvement in programming performances. 37 A reduction in the RESET current of about 55% and in drift coefficient of about 40% in ML devices annealed at 425 °C were observed in comparison with similar devices incorporating the Ge 2 Sb 2 Te 5 reference PCM. Similar trends have been observed in devices based on GST/C MLs.…”
Section: Discussionmentioning
confidence: 77%
“…The annealing conditions (15 minutes at 300°C) were chosen to mimic those encountered during integration into memory devices in our test vehicles. [37] Alternating layers of GeTe and C are observed throughout the stack between the SiO 2 substrate and the SiN capping layer, with well-defined interfaces between the GeTe and C layers. As expected from the R s curve in Fig.…”
Section: Nanostructure Of C-doped Gete Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20] Finally, Sb 2 Te 3 /GeTe, crystalline Sb 2 Te 3 / TiTe 2 , GeTe/C, Ge 8 Sb 92 /Ge, C/Sb, Zn 15 Sb 85 /Ga 30 Sb 70 , and Cr 7 Ge 33 Te 60 /Hf 16 Ge 6 Sb 78 are constructed using two different materials to improve performance using two different properties. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] In this work, an amorphous Sb 2 Te 3 /TiTe 2 heterostructure was fabricated using a magnetron sputtering system at room temperature, and a PCM device was fabricated by introducing the Sb 2 Te 3 /TiTe 2 heterostructure. A PCM was fabricated by inserting several nanolayers of TiTe 2 with low thermal conductivity and high electrical conductivity inside the Sb 2 Te 3 layer with fast switching speed operation characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these results show the potential of iPCMs for applications in neuromorphic computing with high accuracy. By using a same approach than iPCM stacks employing PCM‐based heterostructures, Terebenec et al [ 3 ] demonstrated that integration in memory devices of GeTe 4nm /C 1nm multilayers (MLs) to achieve innovative PCM nanocomposites is a promising system to improve PC memory performance. Indeed, GeTe/C MLs memory devices exhibit significantly reduced programming energy compared with standard PCM devices probably due to an increase of thermal confinement within the memory cell resulting from the reduced thermal conductivity of polycrystalline GeTe/C MLs.…”
mentioning
confidence: 99%